Does birthweight predict bone mass in adulthood? A systematic review and meta-analysis. - Baird, J; Kurshid, M; Kim, M; Harvey, N; Dennison, E; Cooper, C (2011)
SUMMARY: This systematic review and meta-analysis assessed the strength and magnitude of the association between birthweight and adult bone mass. Higher birthweight was associated with higher bone mineral content of the spine and hip in adult men and women at ages between 18 and 80 years across a range of settings. INTRODUCTION: The aim of this review was to assess the strength and magnitude of the association between early size and adult bone mass. METHODS: Systematic review and meta-analysis of studies that assessed the association between birthweight or weight at 1 year, and bone mineral content (BMC) or bone mineral density (BMD) in adulthood. RESULTS: Fourteen studies met inclusion criteria. Nine assessed the relationship between birthweight and lumbar spine BMC, most showing that higher birthweight was associated with greater adult BMC. Meta-analysis demonstrated that a 1 kg increase in birthweight was associated with a 1.49 g increase in lumbar spine BMC (95% CI 0.77-2.21). Birthweight was not associated with lumbar spine BMD in 11 studies. In six studies, considering the relationship between birthweight and hip BMC, most found that higher birthweight was associated with greater BMC. Meta-analysis demonstrated that a 1 kg increase in birthweight was associated with a 1.41 g increase in hip BMC (95% CI 0.91-1.91). Seven studies considered the relationship between birthweight and hip BMD and, in most, birthweight was not a significant predictor of hip BMD. Three studies assessing the relationship between weight at 1 year and adult bone mass all reported that higher weight at one was associated with greater BMC of the lumbar spine and hip. CONCLUSIONS: Higher birthweight is associated with greater BMC of the lumbar spine and hip in adulthood. The consistency of these associations, across a range of settings, provides compelling evidence for the intrauterine programming of skeletal development and tracking of skeletal size from infancy to adulthood.